Sounding the Indian Ocean Musical Circulations in the Afro-Asiatic Seascape - Sykes, Jim; Byl, Julia (University of California Press, 2023)
Sounding the Indian Ocean is the first volume to integrate the fields of ethnomusicology and Indian Ocean studies. Drawing on historical and ethnographic approaches, the book explores what music reveals about mobility, diaspora, colonialism, religious networks, media, and performance. Collectively, the chapters examine different ways the Indian Ocean might be "heard" outside of a reliance on colonial archives and elite textual traditions, integrating methods from music and sound studies into the history and anthropology of the region. Challenging the area studies paradigm-which has long cast Africa, the Middle East, and Asia as separate musical cultures-the book shows how music both forms and crosses boundaries in the Indian Ocean world. "Evocative, wide-ranging, and fascinating. A highly original contribution that charts the way for many future paths of exploration." - RONIT RICCI, author of Islam Translated: Literature, Conversion, and the Arabic Cosmopolis of South and Southeast Asia "Undoubtedly the definitive, standard-bearing work on the deeply cosmopolitan and interconnected soundworlds of the Indian Ocean." DAVESH SONEJI, author of Unfinished Gestures: Devadasis, Memory, and Modernity in South India "A finely crafted voyage that secures the place of ethnomusicological scholarship in the reconstruction of one of the world's oldest long-distance trading arenas." - ANGELA IMPEY, author of Song Walking: Women, Music, and Environmental Justice in an African Borderland "Adeptly shows how music composes and transgresses categories, genealogies, and geographies in Afro-Asiatic seascapes." - SMRITI SRINIVAS, coeditor of Reimagining Indian Ocean Worlds